2009
DOI: 10.1007/s10551-009-0248-0
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Philanthropic Giving, Advertising Intensity, and Industry Competition Level

Abstract: advertising intensity, catastrophic events, corporate philanthropy, corporate social responsibility, industry competition level,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(163 citation statements)
references
References 59 publications
10
149
4
Order By: Relevance
“…3 The inter-rater coefficient in this study is higher than 90 %, which means the reliability of our coding process is admissible. After the coding process, we found Zhang, Rezaee, and Zhu (2009) and Zhang, Zhu, Yue, and Zhu (2010) shared the same samples in their empirical studies. Therefore, we excluded Zhang et al's (2009) study from our database.…”
Section: Sample and Codingmentioning
confidence: 80%
“…3 The inter-rater coefficient in this study is higher than 90 %, which means the reliability of our coding process is admissible. After the coding process, we found Zhang, Rezaee, and Zhu (2009) and Zhang, Zhu, Yue, and Zhu (2010) shared the same samples in their empirical studies. Therefore, we excluded Zhang et al's (2009) study from our database.…”
Section: Sample and Codingmentioning
confidence: 80%
“…Zhang et al (2010) found that the mean and median respectively of corporate contributions in response to Sichuan earthquake (also known as the Great Wenchuan Earthquake) for the 703 Chinese firms studied were 3,086,688 and 1,001,000 RMB (note: 1 million RMB is roughly equivalent to €123, 000). Although the Sichuan earthquake may be a special case, in a more general study of the effects of philanthropic activity on profitability in the Chinese context, Su and He Opening the Black Box of CSR Decision Making (2010) found that the mean donation derived from the sample of 3,837 Chinese private enterprises surveyed (2006 data) was approximately 414,000 RMB (although the median was 50,000 RMB).…”
Section: ------------------------------------------------Insert Figurmentioning
confidence: 99%
“…Corporate philanthropy and other discretionary corporate social initiatives can generate a positive reputation and subsequent positive moral capital among communities and stakeholders if these social initiatives are judged to be made due to a genuine regard for social welfare (Godfrey 2005). 1 The positive moral capital mitigates the negative assessments and resulting sanctions by stakeholders following firms' misconducts, making firms less vulnerable to negative events (Godfrey 2005;Peloza 2006;Zhang et al 2010b). Bhattacharya and Sen (2004) also suggest that investing in CSR helps to build a reservoir of goodwill which leads to stakeholders' resilience to negative information about a company perceived to be socially responsible.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…All these fees are related to activities aimed at promoting sales. Thus, selling expense is an appropriate measure of firms' advertising intensity(Zhang et al 2010b).…”
mentioning
confidence: 99%